Role of underwriters and auditors in earnings forecast accuracy of Singapore IPO prospectus. - Chan, Chuei Mei. (2008)
This paper aims to examine the roles of underwriters and auditors as monitoring devices in IPO. This is examined through the investigation of the accuracy of the earnings forecast provided by the companies in the IPO prospectus.